Processos de conectividade e a vegetação ripária do Alto Rio Paraná-MS - Corradini, Fabrício Anibal (2006)
Large rivers, like Paraná, generally have floodplains which are areas that overflow with a certain frequency. As a result, they form specific ecosystems which show high heterogeneity in the species distribution. The geomorphological features found in the relief along the plain are marked by lowered areas that are generally overflowed every year, shallowness areas of periodical flooding, high areas, active and inactive discharge channels, lakes, crevasse swamps, and antique channels whose origin and dynamics are linked to the hydrological system in a variable time scale. The flooding Pulse, as the biggest strength which controls the plain and river biota, associated to the relief topography are the responsible factors for different connection degrees between the river water and the plain. This study aims at determining the connectivity elements and processes as an abiotic vegetation controller in the floodplain, between Paranapanema mouth and the central part of Baia river, nearby Porto Rico town in Parana state. For such a proposal, it considered the hydrological data between 1964 and 2003 applied to PULSO program which defined FITRAS function features (frequency, intensity, tension, recurrence, amplitude, stationality). The survey of the altimetric cotes represented in 5 transversal profiles through Theodolite Total (Station) and clinometer was considered necessary. The river water level for that day was considered as cote 0 (zero) and the altitude was corrected with the zero of the linimetric ruler of Porto São Jose-PR and with the declivity of Parana River channel. A geomorphological mapping of the area was proposed using photointerpretation of aero photographs in the 1:60.000 scale of May 1996, and a soil sample was collected at each geomorphological unit at depths of 0 - 20, 20 - 40, 40 - 60 cm for the granulometric and soil fertility analysis; and the floristical survey was considered for the study area according to Fachini's stricto sensu work (2001). 6 geomorphological units and 2 sub-units were defined for the plain of the following islands: Unidade Planície Alta (UpA); Unidade planície Baixa (UpB), Unidade de Escoamento (UE), Unidade Planície Alta/ Setor Indiferenciado (UpaSI): Unidade Dique Marginal (UDM) and Unidade Mutum which is subdivided into Sub-unidade Mutum-Alto (SuMA) and Sub-unidade Mutum-Baixo (SuMB). For each unit which showed different altimetric cotes different values of FITRAS function were obtained, thus it was possible to conclude that Parana River control ever the vegetation is due to the soil granulometry which defines the water permanence, and the topographic position of the units which established different connection degrees with Parana river.